Pathogen infection induces sickness behaviors through neuromodulators linked to stress and satiety in C. elegans - Sreeparna Pradhan; Gurrein K. Madan; Di Kang; Eric Bueno; Adam A. Atanas; Talya S. Kramer; Ugur Dag; Jessica D. Lage; Matthew A. Gomes; Alicia Kun-Yang Lu; Jungyeon Park; Steven W. Flavell (Nature Communications)
Abstract When animals are infected by a pathogen, peripheral sensors of infection signal to the brain to induce adaptive behavioral changes known as sickness behaviors. While the pathways that signal from the periphery to the brain have been intensively studied, how central circuits are reconfigured to elicit these behavioral changes is not well understood. Here we find that neuromodulatory systems linked to stress and satiety are recruited during chronic pathogen infection to alter the behavior of Caenorhabditis elegans. Upon infection by the bacterium Pseudomonas aeruginosa PA14, C. elegans decrease feeding, then display reversible bouts of quiescence, and eventually die. The ALA neuron and its neuropeptides FLP-7, FLP-24, and NLP-8, which control stress-induced sleep in uninfected animals, promote the PA14-induced feeding reduction. However, the ALA neuropeptide FLP-13 instead delays quiescence and death in infected animals. Cell-specific genetic perturbations show that the neurons that release FLP-13 to delay quiescence in infected animals are distinct from ALA. A brain-wide imaging screen reveals that infection-induced quiescence involves ASI and DAF-7/TGF-beta, which control satiety-induced quiescence in uninfected animals. Our results suggest that a common set of neuromodulators are recruited across different physiological states, acting from distinct neural sources and in distinct combinations to drive state-dependent behaviors.